The Effect of Creativity and Self-Efficacy on the Performance of Culinary MSMEs with Entrepreneurship Orientation as Mediation - Andreas Antonius; Louis Utama (Graduate Program of Universitas Tarumanagara, 2023)
This study aims to determine the effect of creativity and self-efficacy on the performance of culinary MSMEs with an entrepreneurial orientation as a mediation. The number of samples used in this study were 100 samples who were culinary MSMEs entrepreneurs in West Jakarta. Methods and sampling techniques in this study use non-probability sampling (purposive sampling). Data collection is done online through google forms and in person. The data analysis technique in this research is the SEM-PLS method using the SmartPLS 3.0 software. The results show that creativity affects the business performance of culinary MSMEs, self-efficacy affects the business performance of culinary MSMEs, entrepreneurial orientation affects the business performance of culinary MSMEs, and entrepreneurial orientation does not mediate the two relationships between creativity and self-efficacy on the business performance of culinary MSMEs.